The Place and Role of The Subject "Safety of Life Activities" In the Preparation of Future Environmental Engineers for Professional Activity - Kholdorova Mukhayyo Otakulovna (Genius Journals, 2024)
In this work, the issues of forming a stable interest in life safety and labor protection activities among future environmental engineers who are trained in technical higher education institutions were considered.
Keywords: Life safety; labor protection; specialist; interest